PENGEMBANGAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI PEMBELAJARAN OUTDOOR PADA AREA KEBUN DI TK BUDHI MULYO SARIMULYO CLURING BANYUWANGI - Imam Wahyono; Eka Ramiati; Siti Khalimatus Sa’diyah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Cognitive ability is the ability to learn or think or intelligence, namely the ability to learn new skills and concepts, the skills to understand what is happening in the environment and the memory ability to solve simple problems. Outdoor learning in the garden area is learning where the teaching and learning process is carried out outside the room or classroom area. In the garden area, such as planting seeds and grains which will become flowers, vegetables can even produce food, for example rice. This study aims to determine the cognitive development of early childhood through outdoor learning in the garden area at Kindergarten Budhi Mulyo Sarimulyo, Cluring-Banyuwangi. This type of research is using a qualitative descriptive research method. The subjects of this research were students of class B TK Budhi Mulyo. The results showed that the development of early childhood cognitive abilities through outdoor learning in the garden area at Kindergarten Budhi Mulyo Sarimulyo can optimize early childhood cognitive abilities at Kindergarten Budhi Mulyo, this is due to outdoor learning in garden areas such as: planting, watering plants which are routinely carried out every day both at school and at home, makes children indirectly hone their cognitive abilities almost every day and even every time, therefore the stimulation of cognitive abilities that students get at Kindergarten Budhi Mulyo is much more, so as to get maximum results.